01 Magnum Chronicles : A brief visual history in the time of ISIS. - Van Agtmael, Peter; Harling, Peter (Magnum Photos, [s.l.], 2018)
Terrorisme
Morath, Inge ; Rodger, George ; Gruyaert, Harry ; Majoli, Alex ; Barbey, Bruno ; Towell, Larry ; Saman, Moises ; Dworzak, Thomas ; Sessini, Jerome ; Tavakolian, Newsha ; Meloni, Lorenzo ; Drake, Carolyn ; Pellegrin, Paolo ; Sanguinetti, Alessandra ; van Agtmael, Peter ; Parr, Martin ; Özmen, Emin ; Power, Mark ; Koudelka, Josef
boek